Iodine-mediated oxidative rearrangement of alpha,beta-unsaturated diaryl ketones: a facile access to 1,2-diaryl diketones - Bansode, Ajay H.; Suryavanshi, Gurunath (ACS Omega, 2019)
A metal-free oxidative rearrangement was explored for the synthesis of 1,2-diaryl diketones by utilizing alpha, beta-unsaturated diaryl ketones and I-2/TBHP in good to high yields. The reaction proceeds via oxidative aryl migration, followed by C-C bond cleavage. A simple and high-yielding protocol was developed for the synthesis of a wide range of 1,2-diaryl diketones, which are the backbone for a variety of medicinally important molecules.